2016
DOI: 10.1002/pip.2760
|View full text |Cite
|
Sign up to set email alerts
|

Record amorphous silicon single-junction photovoltaic module with 9.1% stabilized conversion efficiency on 1.43 m2

Abstract: Providing two-thirds of the total stabilized power of thin-film tandem MICROMORPH TM technology, the amorphous junction remains a key element in the quest for higher efficiencies. This paper reports and summarizes a considerable work to achieve a record large-area amorphous silicon single-junction photovoltaic module. New hardware has been developed and known process steps have been accurately tuned and combined with new features of cell design. Effort was focused on the deposition of high-quality and low-defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To overcome such limitation, one can alternatively use doped wide bandgap thin-film Si films alloyed with carbon or oxygen that can induce stronger band bending than doped a-Si:H layers. In fact, a p-type contact stack featuring wide E g,p material such as SiO x :H (1.7 -2.2 eV) [24], [25], [55] and SiC x :H (1.4 -2.1eV) [20], [48], [75] exhibits maximized band bending at c-Si (see Figure 13 (right), where ΔE ~ 0). As a result, the use of wide bandgap doped p-type layer as incubation layer potentially boosts both FF and V OC as reported in Table 2.…”
Section: Band Gap Of Highly-selective P-type Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome such limitation, one can alternatively use doped wide bandgap thin-film Si films alloyed with carbon or oxygen that can induce stronger band bending than doped a-Si:H layers. In fact, a p-type contact stack featuring wide E g,p material such as SiO x :H (1.7 -2.2 eV) [24], [25], [55] and SiC x :H (1.4 -2.1eV) [20], [48], [75] exhibits maximized band bending at c-Si (see Figure 13 (right), where ΔE ~ 0). As a result, the use of wide bandgap doped p-type layer as incubation layer potentially boosts both FF and V OC as reported in Table 2.…”
Section: Band Gap Of Highly-selective P-type Contactmentioning
confidence: 99%
“…Based on thin-film Si alloys, the use of silicon heterojunction (SHJ) structures has become particularly interesting to industry for the low thermal budget fabrication process. Besides, this PV technology benefits from the tremendous experience the field acquired from thin-film Si PV applications, which offer flexibility in a wide range of fabrication parameters [17]- [20]. The combination of c-Si and thin-film Si-based materials has therefore resulted in outstanding V OC values between 740 and 760 mV [15], [21], [22], anticipating record efficiency solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they observed that exposure to the light of an a-Si:H-based solar cell, stretched over time, caused a drop of its electrical parameters: this is known as a lightinduced degradation (LID) effect. This limitation can be reduced by controlling the thickness of the intrinsic (i) layer in the structure of solar cell [13,14]. In the a-Si:H-based solar cell, the thickness of the i-layer controls the short-circuit current [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercially available stabilized efficiency and reliability of a-Si:H solar cells are greater than many of the third generation solar cells as reported so far. However, the main drawback of a-Si:H solar cells is light-induced degradation (LID), which can be minimized by controlling the thickness of the intrinsic (i) layer. Normally, the LID decreases with decreasing the thickness of the i-layer, but the thickness of the i-layer cannot be lowered abruptly to minimize the LID as there are many other factors associated with this layer like absorption of light, etc. Among the three main layers of a-Si:H solar cell, the thickness of the i-layer controls the short-circuit current ( I sc ) and the thickness of the p- and n-layers along with their doping parameters determine the open circuit voltage ( V oc ) and short-circuit current ( I sc ).…”
Section: Introductionmentioning
confidence: 99%